2014
DOI: 10.1007/s00418-014-1279-x
|View full text |Cite
|
Sign up to set email alerts
|

Murine CLCA5 is uniquely expressed in distinct niches of airway epithelial cells

Abstract: The murine mCLCA5 protein is a member of the chloride channel regulators, calcium-activated (CLCA) family and is suspected to play a role in airway mucus cell differentiation. Although mCLCA5 mRNA was previously found in total lung extracts, the expressing cells and functions in the naive murine respiratory tract are unknown. Therefore, mCLCA5 protein expression was identified by immunohistochemistry and confocal laser scanning microscopy using entire lung sections of naive mice. Moreover, we determined mRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…However, its expressing cell type is unknown to date. The Clca2 protein which is expressed in keratinocytes of stratified epithelia and in distinct niches of the respiratory tract [ 48 , 74 ] has not been detected in the intestinal tract to date which is consistent with our findings [ 48 ]. The absence of any differential Clca expression pattern in the mucus on the protein level suggests that the lack of a phenotype may not be due to a phenotype rescue by other Clca homologs.…”
Section: Discussionsupporting
confidence: 91%
“…However, its expressing cell type is unknown to date. The Clca2 protein which is expressed in keratinocytes of stratified epithelia and in distinct niches of the respiratory tract [ 48 , 74 ] has not been detected in the intestinal tract to date which is consistent with our findings [ 48 ]. The absence of any differential Clca expression pattern in the mucus on the protein level suggests that the lack of a phenotype may not be due to a phenotype rescue by other Clca homologs.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigators have suggested that CLCA proteins may act as extracellular signalling molecules 17, 36 and it is tempting to speculatively attribute such as role to mCLCA5 in this context at the invasive edge of the tumour (Figure 7). …”
Section: Resultsmentioning
confidence: 98%
“…17 Of particular interest, both CLCA2 and CLCA4 have been shown to inhibit proliferation of breast cancer cells when ectopically expressed in vitro , 18 whereas normal breast tissue exhibits high levels of CLCA2 in both acini and small ducts. 19 Murine CLCA5 (mCLCA5) is highly homologous to human CLCA2 (hCLCA2) and is considered to be its orthologue.…”
mentioning
confidence: 99%
“…A positive association is observed between murine CLCA1 and CLCA2 and Stat3 activity, whilst Stat3 negatively regulates murine CLCA5, the murine orthologue of human CLCA2 [ 125 ]. The exact functions of CLCA family members within the mammary gland are yet to be determined, but their regulation by Stat3 during the involution period may be pertinent to the pathogenesis of involution-associated mastitis given their postulated modulation of the innate immune response and/or potential activity as signalling molecules [ 126 , 127 ].…”
Section: Involution- or Dry Period-associated Mastitismentioning
confidence: 99%